2002
DOI: 10.1046/j.1365-2249.2002.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of serum tissue inhibitor of metalloproteinase-1 but not metalloproteinase-3 in atopic dermatitis

Abstract: SUMMARY Matrix metalloproteinases and their specific inhibitors, tissue inhibitors of metalloproteinases (TIMPs), contribute to inflammation‐induced tissue destruction and subsequent remodeling for maintenance of tissue homeostasis. Since the production of these enzymes and their inhibitors is regulated by mediators such as proinflammatory cytokines and growth factors, elevated levels of serum TIMPs and/or MMPs have been documented in patients with several inflammatory disorders. In this study, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
1
23
0
2
Order By: Relevance
“…The serum TIMP-1 levels were significantly higher in atopic dermatitis patients in exacerbation status than in non-atopic subjects [28]. Significantly higher values of serum levels of IgE were noted in atopic dermatitis patients with elevated TIMP-1 levels when compared with those with normal values [28]. On the other hand, PGG treatment induced expression of IGFBP-3 and IL-10.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The serum TIMP-1 levels were significantly higher in atopic dermatitis patients in exacerbation status than in non-atopic subjects [28]. Significantly higher values of serum levels of IgE were noted in atopic dermatitis patients with elevated TIMP-1 levels when compared with those with normal values [28]. On the other hand, PGG treatment induced expression of IGFBP-3 and IL-10.…”
Section: Discussionmentioning
confidence: 91%
“…Genetic variation at the eotaxin locus has been correlated with serum total IgE [27]. The serum TIMP-1 levels were significantly higher in atopic dermatitis patients in exacerbation status than in non-atopic subjects [28]. Significantly higher values of serum levels of IgE were noted in atopic dermatitis patients with elevated TIMP-1 levels when compared with those with normal values [28].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Katoch et al found a higher serum level of TIMP-1, but not MMP-3, in a group of patients with exacerbated atopic dermatitis. Additionally, they observed that the level of TIMP-1 is significantly reduced following the treatment of exacerbation [29].…”
Section: A At To Op Pi Ic C D De Er Rm Ma At Ti It Ti Is Smentioning
confidence: 99%
“…Moreover, the patients with chronic eruptions (lichenification and prurigo) had significantly higher TIMP-1 levels, while those with acute lesions were not correlated with TIMP-1 level in the serum. The authors gave a hypothesis that serum TIMP-1 level may be a useful marker to estimate the long-term disease activity of AD (Katoh et al, 2002). Human tissue kallikreins, or kallikrein-related peptidases (KLKs), are the largest family of trypsin-or chymotrypsin-like serine proteases (SPs).…”
Section: Enzymesmentioning
confidence: 99%